Biorecovery of olive mill wastewater sludge from evaporation ponds. (1st October 2022) - Martínez-Gallardo, M.R.; Jurado, M.M.; López-González, J.A.; Toribio, A.; Suárez-Estrella, F.; Sáez, J.A.; Moral, R.; Andreu-Rodríguez, F.J.; López, M.J.
Abstract: Olive mill wastewater (OMW) resulting from the olive oil extraction process is usually disposed of in evaporation ponds where it concentrates generating a sludge that pollutes the ponds nearby area. In this study, four bio-treatments were applied for the in-situ bioremediation and valorization of OMW sludge: Landfarming, phytoremediation, composting and vermicomposting. In all cases, the OMW sludge was added with organic residues (mushroom compost, rabbit manure, and chicken manure). The bio-treatments were carried out in duplicate, inoculated and non-inoculated, to determine the effect of a specialized fungal consortium ( Aspergillus ochraceus H2 and Scedosporium apiospermum H16) on the efficacy of the bio-treatments. The evaluation of chemical parameters, toxicity, and functional microbial biodiversity revealed that the four techniques depleted the toxicity and favored the stimulation of functional microbiota. Landfarming and phytoremediation allowed the decontamination and improvement of soils. Composting and vermicomposting also offered high-quality products of agronomic interest. Inoculation improved the bioremediation effectiveness. Biological treatments are effective for the safe recovery of contaminated OMW sludge into high-quality services and products. Graphical abstract: Image 1 Highlights: Composting transforms Olive Mill Wastewater (OMW) sludge into high-quality product. Landfarming and phytoremediation allow the decontamination of OMW sludge. Vermicomposting promotes microbial functional biodiversity in OMW sludge. Fungal consortium accelerates degradation processes inherent to the bio-treatments. Organic residues added to OMW sludge stimulate microbial activity.